Risk Factors for Urinary Incontinence in the Elderly - Regina, Kezia; Tamba, Ernawaty; Soesanto, Aries (Jurnal MedScientiae, 2024)
Individuals aged sixty years or older who require more care are referred to as seniors. Urinary incontinence in the elderly is a common problem. Uncontrolled urine production is known as urinary incontinence. Elderly people often experience this health problem. As we age, pelvic muscles weaken, resulting in changes in the anatomical function of the urinary tract organs and an increased risk of urinary incontinence. The aim of the research is to review related research on risk factors for urinary incontinence in the elderly. This research uses literature study. Where using a search for journals in Indonesian and English for 2013 - 2023 which was carried out using the WHO, PubMed, NCBI databases with the keywords Urinary incontinence in the elderly and found 10 journals selected according to the inclusion criteria with elderly subjects ≥ 45 years, cross sectional design and descriptive. The results show that urinary incontinence in the elderly has a significant relationship with risk factors for urinary incontinence such as diabetes, smoking, vaginal delivery and quality of life in the elderly. It can be concluded that there is a relationship between the two variables and most studies show that urinary incontinence is an important factor that can cause stress in the elderly.